Sensitivity Analysis of the Effective Reproduction Number in a Sarawak Rabies Epidemic Model - Nur Asheila, Abdul Taib; Jane, Labadin (IEEExplore, 2022)
For past decades, investigations on the transmission dynamics of canine-mediated rabies as well as the best practice for rabies control efforts have utilized mathematical models. In this paper, sensitivity of the effective reproduction number to model parameters is investigated by employing Normalized Forward Sensitivity Index. A Susceptible-Exposed-Infectious-Vaccinated (SEIV) model for rabies is formulated and the effective reproduction number is derived through the Next Generation Matrix method. The sensitivity analysis has identified dog-to-dog transmission rate and rate of newborn dogs as the most impactful parameters that contribute to the number of secondary infections. The result highlighted the significance of dog population management to curtail rabies transmission. This is crucial in aiding public health decision-makers as these influential parameters can be targeted for rabies control and intervention strategies.